2022
DOI: 10.3390/ijerph19063677
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Low-Fat Chocolate Milk on Delayed Onset Muscle Soreness and Performance in Players on a Women’s University Badminton Team

Abstract: This study investigated the short-term effects of low-fat chocolate milk (LFCM) consumption on delayed onset muscle soreness (DOMS) and performance in female badminton players. Seven female badminton players (23 ± 1 years; height: 163.8 ± 4.1 cm; body mass: 58.7 ± 0.9 kg) were randomly assigned to 1 week of LFCM (500 mL) or placebo (water, 500 mL) consumption in a crossover design. Participants consumed LFCM or water immediately after each training session during the 1-week intervention. Performance variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…Our findings were consistent with previous studies that found a higher MGR after a CM trial compared with a CHOPRO trial (Karp et al, 2006) and a placebo trial (Molaeikhaletabadi et al, 2022). In contrast to our study that measured the increase in BUN level as an indicator, Karp et al (2006) measured performances as an indirect indicator of MGR rate among men cyclists.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our findings were consistent with previous studies that found a higher MGR after a CM trial compared with a CHOPRO trial (Karp et al, 2006) and a placebo trial (Molaeikhaletabadi et al, 2022). In contrast to our study that measured the increase in BUN level as an indicator, Karp et al (2006) measured performances as an indirect indicator of MGR rate among men cyclists.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, both drinks had the same amount of CHO and protein; however, the number of calories in CM was higher because it contained fat (12.5 g/500 mL), similar to Molaeikhaletabadi et al (2022) who used fat, but in a lower content (7.5 g/500mL). It has been demonstrated that the fat in CM raises free fatty acid circulation in the bloodstream and thereby inhibits muscle glycogen depletion, acting as a fuel that spares glycogen during exercise, as it has a glycogen-sparing effect (Muscella et al, 2020).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations